Multidimensional Poverty and its Effect on the Economy of Aceh Province - Pratama, Siectio Dicko; Rahadiana, Rizal (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2023)
The first goal of Sustainable Development Goals, eliminating poverty in all forms, is closer to multidimensional poverty rather than official poverty statistics, which are measured using the basic need approach. Examining the trend of economic growth in Aceh during the past few years reveals the limitations of this strategy. Economic improvement has little effect on the poverty rate because it is only measured in one dimension. This research measures the poverty rate from various aspects by examining the forming factors first. The formed index will then be analyzed for its properness by involving other related variables and compared to the basic-need-based poverty measurement. Furthermore, every impact of each dimension on economic growth will also be assessed. Using the confirmatory factor analysis (CFA), multidimensional poverty is measured to give another perspective on the poverty rate. Multiple linear regression is employed to identify the relationship between the poverty dimension and the economy. The result shows that the new poverty rate measurement gives more proper poverty distribution across the region in Aceh Province. Concerning the human development index, multidimensional poverty is more relevant than basic need poverty. Asset ownership and education are the dimensions that significantly affect the economy. Our study concludes that multidimensional poverty should complement the monetary poverty produced by national statistical agencies and provide a new direction of poverty alleviation policy, such as increasing physical investment in households or creating vocational programs to improve the quality of the population.